Azhee: Turning personal grief into collective action against suicide - Sabah Abdulrahman (Intervention Journal of Mental Health and Psychosocial Support in Conflict Affected Areas, 2022)
Suicide is still a taboo issue in Iraqi society. Many in Iraq still feel shame in admitting that they have lost a loved one to suicide for fear of societal stigmatisation. With a lack of understanding about mental illness, it can be even more difficult for professionals to treat mental health issues properly. The cultural norms that stigmatise suicide create obstacles that discourage, or even prevent, many vulnerable people from reaching out for help. While life is full of challenges, suicide prevention is riddled with even more. Suicide prevention requires collective multisectoral intervention, but in the absence of endorsed national strategy, the interventions have been so far short-term and sporadic. Nongovernmental organisations like Azhee are not funded adequately to implement long-term, multisectoral interventions for effective suicide prevention. Different official entities collect and disseminate statistics on suicide, contradicting one another more than often. Absence of credible statistics at regional and national levels adversely affects the quality of interventions. The media in Iraq and its Kurdistan Region report irresponsibly on suicide which serves as a risk factor in relation to suicide. Another challenge is the weakness of coordination among national and international actors working in suicide prevention interventions.